Quantification of expression and methylation of the Igf2r imprinted gene in segmental trisomic mouse model - Vacík, Tomás; Forejt, Jirí (Genomics, 2003)
Insulin-like growth factor 2 receptor (Igf2r), a maternally expressed imprinted gene, is triplicated in Ts43H trisomic mice. To verify its expression in a trisomic mode, we examined the allele-specific transcripts and relative levels of Igf2r mRNA in trisomic and control mice. Igf2r was expressed from the maternal allele(s) and silenced on the paternal allele(s) in most tissues of maternally or paternally derived Ts43H mice. The triallelic expression was observed in adult brain and testis and in embryonic head, but the antisense transcript, Air, was strictly paternal, and methylation of region 2 was strictly maternal in all tissues. The Igf2r expression in maternally derived trisomics, with two active copies of the gene, did not exceed the average mRNA levels of euploid controls with monoallelic expression. Thus, an indication is presented for a dosage compensation mechanism of Igf2r in the trisomic context.
Keywords: Mice; Organ Specificity; antisense RNA; DNA Methylation; receptor IGF typ 2; metylace DNA; Animals; trizomie; genomový imprinting; Trisomy; orgánová specificita; Disease Models, Animal; zvířata; RNA, Antisense; myši; Receptor, IGF Type 2; Genomic Imprinting; modely nemocí na zvířatech